2005
DOI: 10.1038/sj.jea.7500457
|View full text |Cite
|
Sign up to set email alerts
|

Analyses of magnetic-field peak-exposure summary measures

Abstract: Two previous epidemiologic studies reported an association between the maximum magnetic field exposure logged during a 24-h measurement period and risk of miscarriage. A hypothesis was put forth which argued that the observed association may be the result of behavioral differences between women with healthy pregnancies (less physically active) and women with miscarriage. We analyzed four existing data sets with power-frequency magnetic-field personal exposure (PE) measurements to investigate the characteristic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
22
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 10 publications
(17 reference statements)
6
22
1
Order By: Relevance
“…However, if investigators are interested in exposures occurring outside the home only, then more 1 d of sampling would be required to adequately capture the intra-individual variability in exposures that are experienced over time regardless of the selected exposure metric. Others (3,5,7,16,25) have also examined the temporal variability of personal magnetic field exposure metrics in adults and have reported similar findings for the exposure metrics assessed in the present study. Thus, there appears to be consensus across several cohorts that exposure measurement error due to temporal variability is much more problematic for those exposure metrics towards the upper tail of the exposure distribution.…”
Section: Power-frequency Magnetic Field Exposure In Mensupporting
confidence: 81%
See 1 more Smart Citation
“…However, if investigators are interested in exposures occurring outside the home only, then more 1 d of sampling would be required to adequately capture the intra-individual variability in exposures that are experienced over time regardless of the selected exposure metric. Others (3,5,7,16,25) have also examined the temporal variability of personal magnetic field exposure metrics in adults and have reported similar findings for the exposure metrics assessed in the present study. Thus, there appears to be consensus across several cohorts that exposure measurement error due to temporal variability is much more problematic for those exposure metrics towards the upper tail of the exposure distribution.…”
Section: Power-frequency Magnetic Field Exposure In Mensupporting
confidence: 81%
“…sampling days separated by weeks or months). These issues have primarily been explored using data sets in women that integrate exposures both inside and outside the home (3, 7 , 16), or in men and women that integrate exposures inside the home only and have been pooled together (5) . To date, it is unclear how generalisable these studies are to understanding patterns of daily personal magnetic field exposures that occur in men because, when compared with women, there may be important differences related to behaviour, time-activity patterns and resultant exposures.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent publication of your journal, Mezei et al (2006) stated in their abstract and discussion that ''These findings are consistent with the hypothesis suggesting that the association between maximum magnetic fields (MFs) and miscarriage are possibly the result of behavioral differences between women with healthy pregnancies and women who experience miscarriages''. Their conclusion was not supported by their evidence because it did not compare behaviors or MF exposures of women whose pregnancies ended normally or ended with miscarriages.…”
supporting
confidence: 71%
“…The Mezei et al (2006) study and a 2006 study by Savitz (2006) were funded by the Electric Power Research Institute (EPRI) to explore the hypothesis that this association was not a causal association but rather a reflection of increased activity and resulting peak MF exposures among women whose conceptus had died and was about to be expelled. If this explanation were true, the death of the conceptus would somehow cause increased activity thus leading indirectly to the high MF exposure instead of high MFs causing the death.…”
mentioning
confidence: 99%
“…Ingole et al, [34] demonstrated that radiation from mobile phones increased the risk for embryo death in chicken embryos. Thus the question of whether EMF exposure is a risk factor still remains to be answered in future studies [35].…”
Section: Discussionmentioning
confidence: 99%